(3JMQjQ CdaGX GdJfHjgs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s
(3ChdgG (B:s
(3hai GdCUdGM cd Yjf MQe JfGhdgG Ydi GdEWdGb eY EecGfg dG dMQeJgG Ch ESJbOGQgG s
(3BNQgG (B:s
(3jbGd YRhJg Edi cPG hZQjJg hYRhGg YRjkG dZJGf hGdhGh CaUM , hGNJGQ GdeUfa GddZI GdeQLhMI hdG YjH Ydjg hGddg CYde gPG BNQ GdcJGH hGdMeO ddg JYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdESdGejs